Profitability’s Effect on IDX30 Firm Value: The Role of Capital Structure and Firm Size - Ahmad Dika Cavalera Putra Benteng; Wawan Ichwanudin; Emma Suryani (Institute of Advanced Knowledge and Science, 2024)
This study investigates the impact of profitability on firm value, with capital structure serving as a mediating variable and firm size as a moderating variable, focusing on companies listed on the Indonesia Stock Exchange's IDX30 index from 2018 to 2022. A quantitative approach is employed to examine the causal relationships, utilizing secondary data from the financial statements of each company, which were sourced from the firms' official websites or the IDX website. A non-probability sampling method was used to select the companies from the IDX30 index during the specified period. The analysis was conducted using panel data, with descriptive statistics and conditional process Hayes analysis performed through SPSS25 and the Hayes Process. The results reveal that profitability has a positive and significant effect on firm value, while also demonstrating a negative and significant impact on capital structure. Furthermore, capital structure positively influences firm value and mediates the relationship between profitability and firm value. Additionally, firm size moderates the effect of profitability on firm value and the impact of capital structure on firm value. These findings provide insights into the interconnected roles of profitability, capital structure, and firm size in determining firm value among IDX30 index listed companies.